Growth/differentiation 5 promotes the differentiation of retinal stem cells into neurons via Atoh8. Issue 11 (7th May 2019) - Li, Yanxiu; Li, Haibo; Zhang, LuSi; Xiong, Siqi; Wen, ShiJin; Xia, Xiaobo; Zhou, Xia
Abstract: Retinal diseases are characterized by the degeneration of retinal neural cells, and are the main cause of blindness. Although the development of stem cell including retinal stem cell therapies raises hope for retinal neuron replacement, currently, there is still no efficient method to regenerate retinal neurons. To realize the potential roles of the production of retinal neurons, neurotrophic factor direct the differentiation of retinal stem cells should be extensively identified. In this article, we characterized growth/differentiation 5 (GDF5), which caused the activation of Smad signaling, can induce neurogenesis and neurite outgrowth in retinal stem cell differentiation. Moreover, a bHLH transcription factor, Atoh8 modulates the effects stimulated by GDF5. These data suggested that GDF5 regulates neuron differentiation through mediating Atoh8 and help us to understand the pathophysiological function of GDF5 in retinal regeneration. Abstract : GDF5 can induce neurogenesis and neurite outgrowth in neuron differentiation of retinal stem cells. GDF5 regulates neuron differentiation of retinal stem cells through mediating Atoh8.